Os Kinikinau de Mato Grosso do Sul: a existência de um povo indígena que resiste - Bolzan, Aila Villela (2013)
One may approach the Kinikinau through its pottery. Looking to give visibility to their existence, this indigenous people from the Paraguayan Chaco, presently installed in the state Mato Grosso do Sulk, created and recreated survival strategies not to be erased from their own history, receiving in recent times an official recognition that had been once denied. The pottery produced currently by their women, is an example of the strategy driven by them to make it less invisible in the context of indigenous peoples of Mato Grosso do Sul. Without land of their own, living for nearly a century on lands of others for years such as the Kadiwéu Indian Reserve - the Kinikinau people were discovered to be Chané-Guaná or Terena. Nowadays, a small portion of the population struggle for an identity that might be legitimately Kinikinau. This study aims to discuss the aspects that led to the alleged disappearance of the Kinikinau looking for reference in ethnological literature of the twentieth century aiming to partially map their territorial dislocations both in past and present, as well as the intersocietal relations established with the Mbayá-Guaicuru people and finally exploring the role of its pottery as a material evidence that consolidates them their own existence today